Miniaturized Amperometric Glucose Sensors Based on Polymer/ Enzyme Modified Carbon Electrodes in the Sub-Micrometer Scale. Issue 12 (1st January 2018) - Marquitan, Miriam; Bobrowski, Tim; Ernst, Andrzej; Wilde, Patrick; Clausmeyer, Jan; Ruff, Adrian; Schuhmann, Wolfgang
Abstract : Carbon electrodes in the sub-micrometer scale were modified with polymer/enzyme films for the fabrication of miniaturized amperometric glucose sensors. The electrodes were modified by means of electrochemically induced co-deposition of various polymers and glucose converting enzymes by (i) activation of protected crosslinkers and formation of a dense crosslinker-polymer network that is able to entrap the biocatalyst on the electrode surface and by (ii) using an electrodeposition paint that was deposited on chemically modified carbon electrodes upon a basic pH shift. The polymer matrixes were equipped with Os-complexes that act as redox shuttles for the electron transfer between the electrode surface and the entrapped redox enzyme. The polymer/enzyme modified electrodes were active toward the oxidation of glucose with a sensitivity in the pA mM −1 range. A linear current response was observed for a glucose concentration of up to 15 mM depending on the polymer/enzyme combination. Owing to their geometry in the sub-micron range, the developed sensors are expected to measure glucose with minimal invasiveness down to the single cell level.